Conducting neutral gold bisdithiolene complex [Au(dspdt)2]˙. Issue 39 (30th September 2020) - Velho, Mariana F. G.; Silva, Rafaela A. L.; Brotas, Graça; Lopes, Elsa B.; Santos, Isabel C.; Charas, Ana; Belo, Dulce; Almeida, Manuel
Abstract : A gold bisdithiolene complex with a unique crystal structure displays high electrical conductivity at room temperature. Abstract : [Au(dspdt)2 ] (dspdt = 2, 3-dihydro-5, 6-selenophenedithiolate) is an unprecedented example of a neutral gold bisdithiolene complex with a unique structure composed of interacting dimer and trimer chains displaying relatively high electrical conductivity (0.1 S cm −1 at room temperature).